Sex-Specific Transcriptomic Differences in the Immune Cells of a Key Atlantic-Mediterranean Sea Urchin - Pérez-Portela, Rocío; Leiva, Carlos (Frontiers in Marine Science, 2022)
The abundance of the black sea urchin, Arbacia lixula, has been increasing during the last decades likely related to global warming. This thermophilous species has a leading role in maintaining marine barrens in the Mediterranean with the consequent negative impact on macroalgal beds due to its grazing activity. In this study, we used transcriptomic data from coelomocytes (the cell effectors of the immune system) of females and males of this sea urchin to study potential differences in performance between sexes under laboratory conditions. Differential adaptations, responses to environmental stressors, and resistance against pathogens between sexes may lead to different outcomes in the ongoing expansion of this species in the Mediterranean Sea. Differential expression analyses demonstrated the existence of 120 transcripts, corresponding to 119 genes and two isoforms of the same gene, differentially expressed between coelomocytes of females and males, being 73 up-regulated in males and 47 up-regulated in females. The differential expression patterns were retrieved from a diversity of genes that play different roles related to the immune response due to their antibacterial activity, immune cell activation, cell to cell interaction, intracellular signaling, and detoxification functioning, among others. Our results point out a higher energetic demand of male coelomocytes due to a higher immune activity than females, whereas females have more efficient molecular systems to avoid oxidative stress caused by infections. In conclusion, our study provides evidence of sex-based differences in the expression of genes related to the immune and stress responses in coelomocytes of the sea urchin A. lixula.